Sejarah dan Perkembangan Partai Persatuan Pembangunan (PPP) di Kota Taksimalaya dan Partisipasinya dalam Pemilu 2004, 2009 dan 2014 - Subagja, Heri; F, Fajriudin; Lestari, Fathia (Historia Madania: Jurnal Ilmu Sejarah, 2021)
Political parties are a means of citizens' political participation in improving democratic life to elect leaders in order to uphold and realize high ideals by fighting for freedom and justice. PPP is a political party that has the characteristics of being a political party based on Islam and being a big house for Muslims. This study will explain the history of the PPP organization in Tasikmalaya City and the existence of PPP in Tasikmalaya City. Based on the research conducted, it can be concluded as follows; Firstly, the United Development Party (PPP) was founded on January 5, 1973 as a result of the political fusion of four Islamic parties, namely the Nadhlatul Ulama Party, the Indonesian Muslim Party (Parmusi), the Indonesian Syarikat Islam Party (SI), and the Perti Islam Party. This establishment was followed by the establishments in various regions including Tasikmalaya, Secondly, the existence of the United Development Party in Tasikmalaya City from 2004, 2009 & 2014, underwent significant changes, starting from work programs consisting of in the fields of religion, politics, social, economic and education, as well as in the regeneration in the first period amounted to 213 people, 233 people in the second period, 195 people in the third period, and 85 people in the fourth period, while the results of the vote in 2004 were 20, 26% (11 seats), in 2009 18.62% (8 seats) and 2014 23.96% (10 seats). In addition, Kyai also has an important role in the success of PPP in Tasikmalaya City. Keywords: Islamic Party, PPP, Tasikmalaya.